Executive turnover and founder CEO experience: Effect on new ventures' R&D investment - Hyejin Cho; Pyoungsoo Lee; Choong Ho Shin (Economies, 2022)
As the direction and strategies of new ventures depend on the top management team (TMT)'s stability and continuous efforts, we investigate the relationship between executive turnover and research and development (R&D) investment investment. Furthermore, we assess the moderating role of the founder chief executive officer (CEO)'s prior experiences to show that founders' experiential knowledge mitigates the adverse side effects of executives' departure. Our empirical analysis utilizes a large pool of firm-level survey datasets comprising 1897 Korean founder-led ventures. The empirical results show that executive turnover reduces R&D intensity, suggesting that new ventures' longer-term investments may be affected by the instability of the management team. We also show that the negative effects of executive turnover weaken when the founder CEO has a longer prior work experience, prior business group experience, and founding experience. Our findings show that the founder CEO's entrepreneurship based on valuable prior experiential knowledge mitigates the negative impact of organizational instability. While the TMT factor is essential for a new venture's survival, our findings show that the manner in which leaders act should also be considered separately.
Keywords: 330; executive turnover; founder CEO; managerial experience; new venture; R&D intensity; top management team